Dephosphorylation of γH2AX by WIP1: An important homeostatic regulatory event in DNA repair and cell cycle control - Moon, Sung-Hwan (2010)
DNA double strand breaks are a particularly toxic form of DNA damage and the mammalian cell has evolved an intricate set of responses to repair this type of DNA lesion. A key early event in the DNA damage response (DDR) is ATM phosphorylation of the histone variant H2AX at serine 139 at the site of the DNA break. Phosphorylated S139 H2AX, or γH2AX, forms a docking site for binding of MDC1, leading to sustained recruitment of other DNA repair factors that mediate the repair of the DNA double strand break. Moreover, recruitment of MDC1 to the break site activates cell cycle checkpoints, protecting the cell from replication of damaged DNA templates. While the molecular events leading to DNA double strand break repair have been well described, the deactivating or homeostatic mechanisms following completion of repair remain largely unexplored. Recent publications by our laboratories and the Medema laboratory shed new light on this issue. Both publications showed that the Wild-type p53-Induced Phosphatase 1 (WIP1) directly dephosphorylates γH2AX. WIP1 migrates to the sites of irradiation-induced foci (IRIF), though at a delayed rate relative to MDC1 and mediates γH2AX dephosphorylation, presumably after DNA repair is complete. This prevents recruitment of other repair factors such as MDC1 and 53BP1 to the DNA damage sites and promotes the dissolution of IRIF. In addition, overexpression of WIP1 has a suppressive effect on DNA double strand break repair. Taken together, these reports further implicate WIP1 as a critical homeostatic regulator of the DDR.